2003
DOI: 10.1007/s00268-003-6780-7
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Reflux Esophagitis Observed by Routine Endoscopic Examination after Gastric Pull‐up Esophagectomy

Abstract: A gastric tube has been widely used for reconstruction of the esophagus after esophagectomy for esophageal cancer. Reflux esophagitis after esophagectomy is frequently observed. Therefore we retrospectively investigated the risk factors for reflux esophagitis after gastric pull-up esophagectomy in 74 outpatients with thoracic esophageal cancer. Reflux esophagitis was diagnosed endoscopically. Esophagitis was classified according to the Los Angeles classification. Reflux symptoms, medications, and the surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 10 publications
9
73
1
1
Order By: Relevance
“…For instance, the prevalence of reflux symptoms after esophagectomy in prospective studies ranged from 20-80% with documented 6 endoscopic evidence of reflux esophagitis in 23-72%, compared with 10.7% in our study. [12][13][14][15][16][17] Dumping after esophagectomy was reported in prospective studies at a 8 rate of 78% compared with 6% recorded in primary care. 18 Steatorrhea was recorded in primary care in 0.2% of patients while in other series it was as high as 70%.…”
Section: The Effect Of Postoperative Symptoms On Psychiatric Morbiditmentioning
confidence: 99%
“…For instance, the prevalence of reflux symptoms after esophagectomy in prospective studies ranged from 20-80% with documented 6 endoscopic evidence of reflux esophagitis in 23-72%, compared with 10.7% in our study. [12][13][14][15][16][17] Dumping after esophagectomy was reported in prospective studies at a 8 rate of 78% compared with 6% recorded in primary care. 18 Steatorrhea was recorded in primary care in 0.2% of patients while in other series it was as high as 70%.…”
Section: The Effect Of Postoperative Symptoms On Psychiatric Morbiditmentioning
confidence: 99%
“…We conducted esophagectomy with enlarged proximal gastrectomy (gastric tube) and yearly endoscopy, as experts recommend. We noted that Group A, which was devoid of PPI, showed a greater number of complications due to acid and bile reflux 25,27,28,40 . In addition, our statistical calculations emphasize the use of omeprazole (Group C) as the most significant independent variable correlated with reduced complications of mixed reflux (erosive esophagitis and Barrett's esophagus -Group A) in the univariate analysis, showing a statistically significant difference (Table 2).…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…We stress the utmost importance of the clinical follow-up and annual endoscopic exam of patients undergoing esophagogastroplasty, combined with the continued use of proton pump inhibitors, beginning in the early postoperative period in an attempt to decrease tumor development in the remaining esophageal stump 26,33,35,[40][41][42][43] . The results obtained in this study, with 50 Chagas megaesophagus patients, support the conclusion that the use of omeprazole (40 mg/day) reduced the onset of erosive esophagitis and Barrett's esophagus during the late postoperative period.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gutshow [11] showed that 38.5% of patients had reflu x esophagitis in the remnant esophagus for three years or more after esophagectomy. Using the Los Angels classification ( Table 1), Shibuya observed sever esophagitis (grade C or D) in 75% o f their patients [17]. In another series of 48 patients , Yamamoto [18] found reflu x esophagitis in 27 o f their 48 patients (56.3%) and majority (70%) had a Los Angeles C or D damage.…”
Section: Reflux Esophagitismentioning
confidence: 97%